A mixed methods research approach to exploring teacher participation in an online social networking website - Kamalodeen, Vimala Judy; Jameson - Charles, Madgerie (University of Alberta, International Institute for Qualitative Methodology, 2016)
Social networks are becoming very prominent in educational discourse. The discourse centers on the role of social media and its utility in the teaching and learning environment. Several arguments have been made to support its use because they are highly collaborative, easily accessible, and provide opportunities to embed a variety of Web 2.0 tools such as blogs, wikis, and online chats. However, there is a dearth in research on teacher use of educational social networking sites (SNS) in Trinidad and Tobago. The purpose of this study was to explore how 35 secondary school teachers in Trinidad and Tobago participated in an educational online social networking site. This study utilized a mixed methods exploratory approach and allowed for the use of online data capture together with questionnaires and interviews. Combined data analysis revealed five different levels of site participation, with most teachers adopting the role of content consumer rather than of content producer. Barriers to participation were time, motivation, technology, and usability. The designed social networking site allowed teachers to make public their discourse on their practice while connecting with colleagues from other schools. The study was qualitative dominant, with the mixed methods research approach allowing for deeper exploration of teachers’ participation on this social networking website, and was justified by the newness and transient nature of data from social networking websites.
Keywords: Mixed methods; Educational social networking sites; Online participation